Temperature Profile in the Bare Ice Area Near the Yamato Mountains, Antarctica - Nishio, Fumihiko; Mae, Shinji (1979)
P(論文) The temperature profile of the ice sheet in the bare ice area (Meteorite Ice Field) near the Yamato Mountains (72°S, 36°E) was calculated on the basis of the heat conduction theory under the steady state condition. The effect of the geothermal heat flux, the vertical velocity of ice mass and the ice thickness on the temperature profile was examined. The analysis of the profile in the past stages of the ice sheet fluctuation showed that before the Fukushima ice stage (about (10)^4 years B.P.) the upward velocity and the ablation rate were approximately zero or the downward motion of ice mass and accumulation might have occurred. This result is completely different from the present state (upward velocity 5cm/year and ablation rate 5cm/year), which suggests that most of the Yamato meteorites collected in 1969-1975 were exposed on the surface of the area after the Fukushima stage. departmental bulletin paper